Synthesis of CuInSe2 thin films from electrodeposited Cu11In9 precursors by two-step annealing - Tsung-Wei Chang; Shao-Yu Hu; Wen-Hsi Lee (Journal of Electrochemical Science and Engineering, 2014)
In this study, copper indium selenide (CIS) films were synthesized from electrodeposited Cu-In-Se precursors by two-step annealing. The agglomeration phenomenon of the electrodeposited In layer usually occurred on the Cu surface. A thermal process was adopted to turn Cu-In precursors into uniform Cu11In9 binary compounds. After deposition of the Se layer, annealing was employed to form chalcopyrite CIS. However, synthesis of CIS from Cu11In9 requires sufficient thermal energy. Annealing temperature and time were investigated to grow high quality CIS film. Various electrodeposition conditions were investigated to achieve the proper atomic ratio of CIS. The properties of the CIS films were characterized by scanning electron microscopy (SEM), X-ray Diffraction (XRD), and Raman spectra.